Causal Relationship Model of Factors Affecting Digital Engagement, Perceived Value and Engagement Experience on Behavioral Intention in Muay Thai Activities among Generation Z - Piromkam, Passapong; Phonsri, Nuttavut; Kaewjaratwirat, Torsak (Ratchaphruek Journal, 2026)
This study aimed to: 1) examine the causal relationships among digital engagement, perceived value, and engagement experience influencing behavioral intention to participate in Muay Thai activities among Generation Z; 2) analyze the mediating role of engagement experience; and 3) explore strategies for enhancing behavioral intention to participate in Muay Thai activities. A mixed-methods research design was employed. In the quantitative phase, the sample consisted of 400 Generation Z undergraduate students from seven public universities in Nakhon Pathom Province, selected through quota and convenience sampling. Data were collected using a structured questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). In the qualitative phase, 20 participants were purposively selected, and data were collected through focus group discussions and analyzed using content analysis. The findings suggest that digital engagement and perceived value significantly shape engagement experience, which acts as a central antecedent of behavioral intention. Engagement experience provides full mediation in the link between digital engagement and behavioral intention, whereas it offers partial mediation in the link between perceived value and behavioral intention. Qualitative evidence confirmed that the integration of sport, cultural elements, and digital technologies enhances the Muay Thai experience and contributes to the sustainable strengthening of Thailand’s soft power.